Comparing yeast genome assemblies - Siow, Cheuk Chuen (2011)
The recent transition to Next-Generation Sequencing technology has accelerated the growth of genome projects exponentially. This explosion includes a multitude of species with different strains/individuals being sequenced and made available to the scientific community. As time passes, errors in genome assemblies are also being discovered and corrected. Biologists need to update their working assembly to a newer version or to convert between different strains or species for comparisons. The LiftOver utility in the UCSC Genome Browser handles these tasks with ease. Unfortunately, the choice for yeast genome conversions is limited. Here, I extend the capabilities of LiftOver by developing applications that generate the chain files required by LiftOver in an efficient way. These files are then utilised by a website that I built to allow conversion between assemblies, strains, or species of yeast using LiftOver. Also, I used R to produce dot-matrix plots of sequence alignment for rapid comparative analysis of a new genome sequence.